The association between feeding patterns and stunting status of children aged 36 to 59 mohts in Bolikhamxai province, Lao P.D.R. - Manithip, Chantanom
This study utilized secondary data from a case-control study, which was conducted during the period 2000 - 2001 in preparation for a nutritional program for local health services of Bolikhamxai province, Lao P.D.R. The aim of the study was to determine the association between feeding pattern and stunting among children aged 36 to 59 months in Bolikhamxai province, Lao P.D.R. The study sample was composed of 120 cases and 125 controls. The associations of two exposure variables, viz., the "duration of breastfeeding" and the "age when table foods were given" to stunting status of the children were investigated. Although the association between stunting status and the duration of breastfeeding was not shown to be statistically significant after adjusting for the age when table foods were given, father's ability to write, number of children in the family and the caloric contribution from carbohydrate, the trend that breastfeeding longer that twelve months is apparently negatively associated with stunting among poor children (OR=0.3, 95% CI=0.06, 1.6) and positively associated to this outcome among children in the middle/high economic level (OR=2.3, 95% CI=2.3, 95% CI=0.72, 7.4) is worth noting. Similarly, the association between stunting and the "age when table foods were given" which was "measured as age when meat was first given" was also not statistically significant (OR=0.86, 95% CI=0.44, 1.68 for the group [less than] 6 months and OR=1.21, 95% CI=0.68, 2.15 for the group [greater than] 8 months). In view of the methodologic issue that could have been opeational, further studies should be conducted to elucidate the role of duration of breastfeeding and initiation of table foods on the occurrence of stunting. Pending the results of a better designed study, Lao mothers should be advised that they may breastfeed their infants beyond the period of infancy but they should also adhere closely to the WHO and UNICEF recommendations concerning food supplementation.